Rationale and protocol of the MetNET-1 trial, a prospective, single center, phase II study to evaluate the activity and safety of everolimus in combination with octreotide LAR and metformin in patients with advanced pancreatic neuroendocrine tumors. Issue 6 (November 2014) - Pusceddu, Sara; de Braud, Filippo; Concas, Laura; Bregant, Cristina; Leuzzi, Livia; Formisano, Barbara; Buzzoni, Roberto
Abnormal PI3K-AKT-mTOR pathway signalling and autocrine activation of the mTOR pathway, mediated through insulin-like growth factor-1, have been implicated in the proliferation of pancreatic neuroendocrine tumor (pNET) cells. Everolimus, an mTOR inhibitor, has shown antitumor benefit in pNETs alone and in combination with octreotide LAR in RADIANT-1 and RADIANT-3 studies. Although everolimus-based phase II/III trials have improved progression-free survival for pNET, its use has not impacted on prolonging overall survival. Metformin has recently shown some anti-cancer activity in both in vitro and in vivo studies by its indirect properties to decrease insulin and insulin-like growth factor-1 (IGF-1) levels and by its antitumour effect to promote AMPK activation and consequently inhibition to TSC1–2/mTOR complex. In light of even more retrospective evidence of metformin's anticancer activity, a prospective evaluation is required to either confirm or discard these preliminary findings. With the aim to evaluate the antiproliferative effect of metformin in combination with everolimus and octreotide LAR in pancreatic well-differentiated neuroendocrine tumor patients, a single arm, prospective, single center phase II study was designed (MetNET-1 trial, NCT 02294006). Forty-three patients are expected to be evaluated. The study is ongoing, and recruitment is estimated to be completed in August 2016. The results will be anticipated in 2017.